Quality of life assessment glaucoma patients based on glaucoma symptom scale and glaucoma quality of life-15 score at M. Djamil Hospital Padang - Fitratul Ilahi; Rince Liyanti (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Objective : To determine the Quality of Life glaucoma patients using Glaucoma Symptom Scale(GSS) and Glaucoma Quality Of Life-15 Score (GQL-15) Method : This was a cross sectional study. Subjects were patients diagnosed with primary glaucoma, aged >18 years, and able to fully comprehend the quiz on their regular visits. One hundred glaucoma patients were evaluated for their symptoms using Glaucoma Symptom Scale (GSS), and their ability to perform daily activities using the Glaucoma Quality of Life-15 Questionnaire (GQL-15). We analyze the correlation between the age, sex, visual acuity, medical and surgical treatment to the patients’ quality of life. Results: Data shows that there were significant differences between the visual GSS and the GQL- 15 score among respondents with unilateral blindness, bilateral blindness, and no blindness, which is patients with bilateral blindness have the worsen quality of life. The other GSS and GQL-15 statistical test showed no significant result. Conclusion: Quality of life assesment in glaucoma patient is an essential part to provide the most suitable and convenient treatment both in terms of vision and also improving their quality of life. GSS and GQL-15 were the suitable instrument to asses and determine the Quality of Life glaucoma patient in clinical practice.